Health Information, the Fair Information Principles and Ethics - Kluge, E.-H.W. (Methods of Information in Medicine, 1994)
If advanced electronic patient records are construed as epistemic patient analogues in information space, then the traditional property-model of patient records is longer appropriate. A new paradigm is required. This paper suggests a new paradigm, examines its ethical implications and explores ways in which these could be reflected in legal and regulatory mechanisms. Special attention is paid to privacy, security and access relative to the so-called “fair information principles”.
Keywords: Electronic Patient Record; Fair Information Principles; Ethics